2021
DOI: 10.1002/adma.202005562
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Activatable Photo‐Extracellular Vesicle for Synergistic Trimodal Anticancer Therapy

Abstract: Extracellular vesicles (EVs) hold great potential in both disease treatment and drug delivery. However, accurate drug release from EVs, as well as the spontaneous treatment effect cooperation of EVs and drugs at target tissues, is still challenging. Here, an engineered self‐activatable photo‐EV for synergistic trimodal anticancer therapy is reported. M1 macrophage‐derived EVs (M1 EVs) are simultaneously loaded with bis[2,4,5‐trichloro‐6‐(pentyloxycarbonyl) phenyl] oxalate (CPPO), chlorin e6 (Ce6), and prodrug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 54 publications
0
69
0
Order By: Relevance
“…Several researches reported that M2 macrophage promoted the migration and invasion of ESCs, angiogenesis, and fibrosis in endometriosis ( 11 13 , 15 , 44 ). Previous studies have demonstrated the antitumor efficacy associated with switching from the M2 to the M1 phenotype ( 5 , 45 ). In this study, we confirmed that M1NVs could effectively reprogram M2 macrophages into M1 macrophages both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Several researches reported that M2 macrophage promoted the migration and invasion of ESCs, angiogenesis, and fibrosis in endometriosis ( 11 13 , 15 , 44 ). Previous studies have demonstrated the antitumor efficacy associated with switching from the M2 to the M1 phenotype ( 5 , 45 ). In this study, we confirmed that M1NVs could effectively reprogram M2 macrophages into M1 macrophages both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are nanosized membranous vesicles produced by most kinds of cells [ 14 ]. They are enclosed by a lipid bilayer that surrounds an aqueous core containing proteins, lipids, and nucleic acids [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with unpolarized macrophages, M1 cells can produce nitric oxide (NO), interleukin-12 (IL-12) and other cytokines to exert effective anticancer effects. 42,43 Thus, we first measured NO generation using a luminescent probe. 44 After macrophages were subjected to different treatments for 12 h, the culture medium in the different groups was collected and centrifuged.…”
Section: Stimulated Differentiation Of Pm0 Cells From the M0 To M1mentioning
confidence: 99%